2005
DOI: 10.1111/j.1365-2486.2005.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation of phenological growing season and climate change impacts in temperate eastern China

Abstract: Using phenological and normalized difference vegetation index (NDVI) data from 1982 to 1993 at seven sample stations in temperate eastern China, we calculated the cumulative frequency of leaf unfolding and leaf coloration dates for deciduous species every 5 days throughout the study period. Then, we determined the growing season beginning and end dates by computing times when 50% of the species had undergone leaf unfolding and leaf coloration for each station year. Next, we used these beginning and end dates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
128
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(145 citation statements)
references
References 54 publications
12
128
2
3
Order By: Relevance
“…Some authors have also stressed the role of soil temperature as the prime factor determining the timing of the onset of boreal, deciduous forests and temperate conifer photosynthesis (Schwarz et al, 1997;Jarvis and Linder, 2000;Baldocchi et al, 2005). Chen et al (2005) found that the spatial patterns of beginning and end dates of growing season correlated significantly with the spatial patterns of mean air temperatures in spring and autumn, respectively, in temperate eastern China, and temperature during the growing season usually did not reach the level that incurred strong negative temperature effects on photosynthesis. In our study, temperature index had little impact on GPP during the growing season, in agreement with field observations (Polley et al, 1992;Bassow and Bazzaz, 1998).…”
Section: Environmental Controls On Daily Gppmentioning
confidence: 99%
“…Some authors have also stressed the role of soil temperature as the prime factor determining the timing of the onset of boreal, deciduous forests and temperate conifer photosynthesis (Schwarz et al, 1997;Jarvis and Linder, 2000;Baldocchi et al, 2005). Chen et al (2005) found that the spatial patterns of beginning and end dates of growing season correlated significantly with the spatial patterns of mean air temperatures in spring and autumn, respectively, in temperate eastern China, and temperature during the growing season usually did not reach the level that incurred strong negative temperature effects on photosynthesis. In our study, temperature index had little impact on GPP during the growing season, in agreement with field observations (Polley et al, 1992;Bassow and Bazzaz, 1998).…”
Section: Environmental Controls On Daily Gppmentioning
confidence: 99%
“…Zheng et al (2002) showed that the response of phenophase advance (or delay) to temperature change was nonlinear, and that phenophase advance differs between northern and southern China. Similarly, by combining NDVI and meteorological data in temperate eastern China from 1983 to 1992, Chen et al (2005) found that the GS was extended by 1.4-3.6 days/year north of 32°N, but shorter south of that latitude. Schwartz and Chen (2002) noted no apparent change in the onset of spring growth in China over the period .…”
Section: Gs Changes In Chinamentioning
confidence: 99%
“…Phenological studies by Chinese researchers using remotely sensed data have since confirmed that growing seasons are lengthening by 1.4-3.6 days per year in the north part of eastern China, and by 1.4 days per year across the entire eastern China on average from 1982 to 1993 (Chen et al 2005). Observed phenological data have proved there are different response patterns of Electronic supplementary material The online version of this article (doi:10.1007/s11284-011-0830-7) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%